Europe and Central Asia Economic Update, October 2015 : Low Commodity Prices and Weak Currencies - World Bank (Washington, DC, 2015)
Against the backdrop of a weakening global economy and volatility in international financial markets, countries of the Europe and Central Asia region (ECA) are transitioning to a new normal that is characterized by low commodity prices, slow trend growth of global trade and less abundant availability of international liquidity. The transition is challenging because the region has not still fully recovered from the after-effects of the global financial crisis and current volatile conditions in international financial markets create headwinds.